2010
DOI: 10.1021/ja906667x
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Induced Self-Assembly of Small Organic Molecules into Ultralong Microbelts with Electronic Conductivity

Abstract: The principle of polymer-controlled crystallization of inorganic materials has been successfully transferred to functional aromatic organic dyes, in this instance 3,4,9,10-perylenetetracarboxylic acid potassium salt (PTCAPS), after its single-crystal structure was determined. The cationic double hydrophilic block copolymer poly(ethylene glycol)-block-branched-poly(ethyleneimine) (PEG-b-PEI) was used as the polymer additive to modify the crystallization of PTCAPS. Ultralong hierarchically structured PTCAPS micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
76
1
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 54 publications
2
76
1
3
Order By: Relevance
“…reported that a specific conductivity was obtained on the iso-oriented assembly of functional aromatic organic dyes. 110) A remarkably high electronic conductivity was observed on ultralong microbelts consisting of primary nanoparticles. Koumoto et al proposed that SrTiO 3 -based mesocrystals exhibit an excellent thermoelectric property due to a two-dimensional electron gas grain boundary.…”
Section: Electrical Propertymentioning
confidence: 99%
“…reported that a specific conductivity was obtained on the iso-oriented assembly of functional aromatic organic dyes. 110) A remarkably high electronic conductivity was observed on ultralong microbelts consisting of primary nanoparticles. Koumoto et al proposed that SrTiO 3 -based mesocrystals exhibit an excellent thermoelectric property due to a two-dimensional electron gas grain boundary.…”
Section: Electrical Propertymentioning
confidence: 99%
“…Based on pH titration results, one carboxylic acid group was still protonated and only 3 groups in the salt form. 19 Because the solubility of PTCAPS in water is very high and it is practically insoluble in many organic media, we used a facile recrystallization method to prepare crystals of PTCAPS from ethanol/water mixed solvents. The precursor PTCAPS molecules dissolve in mixed solvents at higher temperature and precipitate as the temperature decreases because the solution is supersaturated at the lower temperature.…”
mentioning
confidence: 99%
“…In fact, it was reported that perylene has both the α and β polymorphs. 16(b) The single crystal structure of the stable PTCAPS β-polymorph has been published previously, 19 while we were not able to collect a big-enough single crystal of the α-polymorph being stable long enough to determine its single crystal structure.…”
mentioning
confidence: 99%
See 2 more Smart Citations